An interdisciplinary approach to management of diastemas: A novel classification and a case report - Sindhu Saeralaathan; Vamsi Lavu; Mathan Rajan; S K Balaji; Arathi Ganesh (Wolters Kluwer Medknow Publications, 2021)
Diastema between the teeth negatively affects the patients' smile, psychology and daily activities by creating a disharmony in the patients' face. The development of diastema has been attributed to several factors such as labial frenulum, microdontia, mesiodens, peg-shaped lateral incisors, agenesis, cysts, habits such as finger sucking, tongue thrusting, or lip sucking, dental malformations, genetics, proclinations, dental-skeletal discrepancies, and imperfect coalescence of interdental septum. Patients often present with complex problems that require a multidisciplinary treatment approach which includes determination of the aetiological factors, soft tissue morphology, occlusion, patient demands and aesthetic consideration to achieve satisfactory outcomes. Lack of current literature on classification of diastemas and multi-disciplinary approach of management led to the proposal of a new classification the ATAC (Anatomic and Therapeutic Classification) for management of the diastema. This case report highlights the use of the proposed classification for management of diastemas, requiring a perio-restorative intervention using a Chu's proportion gauge to achieve ideal aesthetics.